Declining Enrollment in Long-Term Engineering Programs: Stakeholders’ Perspectives - Baral, Durga Prasad (Journal of Technical and Vocational Education and Training, 2024)
This study investigates the declining enrollment in long-term engineering programs under the Council for Technical Education and Vocational Training (CTEVT) in Nepal, a critical issue affecting the development of skilled human resources and socio-economic transformation. The study analyzes enrollment data over the past 4 to 5 years and assesses enrollment trends. It also incorporates insights from focus group discussions and interviews with various stakeholders, identifies underlying causes of low enrollment, and proposes actionable recommendations. The findings reveal a multifaceted decline influenced by contextual factors, such as socio-economic conditions, the allure of foreign education, and the diminishing value of Technical and Vocational Education and Training (TVET). At an institutional level, issues include haphazard extension of TVET institutions, weakened instructional quality and inadequate industry linkages. Personal perceptions also contribute that vocational education is often seen as a less prestigious alternative to general education. The study's comprehensive analysis culminates in recommendations as suggested by the research participants focused on curriculum revision, strengthening industry linkages and enhancing the overall perception and quality of TVET programs. These insights are crucial for policy formulation, educational reforms, and aligning TVET with industry needs and student aspirations in Nepal.